The impact of the choice of internationalization mode on the financial reporting of the company - Savela, Tanja (My University, 2025)
The study is a case study conducted for Hycamite TCD Technologies Ltd., a company planning international expansion, particularly into the United States. This expansion requires attracting investors and complying with international financial reporting standards, such as IFRS and US GAAP. Currently, the company reports under FAS standards and does not yet have a corporate group structure. It is considering either establishing a wholly owned subsidiary or forming a joint venture, both of which have financial reporting implications. It also explores what factors influ-ence the choice of entry mode in Born Globals. The study examines key differences between IFRS and US GAAP, particularly regarding consolidation and ownership structures. IFRS 10 regu-lates the consolidation of subsidiaries into group financial statements, while IFRS 11 addresses the reporting of joint arrangements. These standards differ from FAS and US GAAP require-ments. The research is based on a literature review, written data, and interviews, which were used to deepen the understanding of the practical application of these standards. IFRS and US GAAP differ in several ways. IFRS is principles-based, providing more flexibility in interpretation, whereas US GAAP is rules-based, offering strict guidelines. In financial statement presentation, IFRS allows expenses to be classified by either function or nature, while US GAAP does not man-date a specific classification method but follows SEC requirements. Revenue recognition under US GAAP follows detailed, industry-specific guidelines, ensuring revenue is only recognized when the earnings process is complete, whereas IFRS applies broader principles emphasizing the transfer of risks and rewards to the buyer. Regarding the definition of control, IFRS deter-mines control based on the ability to influence decisions and obtain financial benefits, even without majority ownership, while US GAAP typically applies a 50% voting power threshold to establish control. In joint arrangements, IFRS 11 distinguishes between joint operations and joint ventures, each with different reporting methods, whereas US GAAP mainly applies the equity method. In financial statement presentation, IFRS mandates certain minimum line items in the balance sheet but does not specify their order, while US GAAP allows greater flexibility. Further-more, IFRS requires convertible debt instruments to be separated into debt and equity compo-nents, whereas US GAAP classifies them entirely as liabilities. The study’s findings confirm the theoretical analysis and provide deeper insights, particularly regarding practical applications. The differences between IFRS and US GAAP significantly impact financial reporting, investor de-cisions, and corporate strategies in international markets. Hycamite must carefully assess the implications of transitioning to IFRS and ensure compatibility with US GAAP if its U.S. entities report under this standard. The study highlights how IFRS and US GAAP differences affect busi-nesses, investors, and regulators. These variations influence financial statement transparency, comparability, and strategic decision-making for companies operating in international markets. Tutkimus on Hycamite TCD Technologies Ltd. -yritykselle tehty tapaustutkimus. Yritys suun-nittelee kansainvälistä laajentumista erityisesti Yhdysvaltoihin, joka edellyttää sijoittajien houkuttelemista ja kansainvälisten tilinpäätösstandardien, kuten IFRS:n ja US GAAP:n, nou-dattamista. Tällä hetkellä yritys raportoi FAS-standardien mukaisesti eikä sillä ole vielä kon-sernirakennetta. Se harkitsee joko kokonaan omistamansa tytäryhtiön perustamista tai yh-teisyrityksen muodostamista, joilla molemmilla on vaikutuksia tilinpäätösraportointiin. Tutki-muksessa tarkastellaan myös, mitkä tekijät vaikuttavat Born Globals -yritysten markkinoille tulon valintaan. Tutkimuksessa tarkastellaan IFRS- ja US GAAP -standardien keskeisiä eroja, erityisesti konsolidoinnin ja omistusrakenteiden osalta. IFRS 10 säätelee tytäryhtiöiden kon-solidointia konsernitilinpäätöksissä, kun taas IFRS 11 koskee yhteisyritysten raportointia. Nämä standardit poikkeavat FAS- ja US GAAP -vaatimuksista. Tutkimus perustuu kirjallisuus-katsaukseen, toissijaisiin lähteisiin ja haastatteluihin, joita käytettiin syventämään ymmär-rystä näiden standardien käytännön soveltamisesta. IFRS ja US GAAP eroavat toisistaan useilla tavoilla. IFRS on periaatteisiin perustuva, mikä tarjoaa enemmän joustavuutta tulkinnassa, kun taas US GAAP on sääntöihin perustuva. Tilinpäätöksen esittämisessä IFRS sallii kulujen luokittelun joko toiminnon tai luonteen mukaan, kun taas US GAAP ei määrää tiettyä luokit-telumenetelmää, vaan noudattaa SEC:n vaatimuksia. US GAAP:n mukainen tulojen kirjaami-nen noudattaa yksityiskohtaisia, toimialakohtaisia ohjeita, jotka varmistavat, että tulot kirja-taan vasta, kun tulojen syntyminen on päättynyt, kun taas IFRS soveltaa laajempia periaat-teita, joissa korostetaan riskien ja hyötyjen siirtymistä ostajalle. Määritelmän osalta IFRS mää-rittää määräysvallan perustuen kykyyn vaikuttaa päätöksiin ja saada taloudellista hyötyä, vaikka enemmistöomistusta ei olisikaan, kun taas US GAAP soveltaa tyypillisesti 50 prosentin äänioikeuden kynnystä määräysvallan määrittämiseen. Yhteisjärjestelyissä IFRS 11 erottaa toisistaan yhteistoiminnot ja yhteisyritykset, joille kummallakin on erilaiset raportointimene-telmät, kun taas US GAAP soveltaa pääasiassa pääomaosuusmenetelmää. Tilinpäätöksen esit-tämisessä IFRS määrää taseeseen tietyt vähimmäiskirjaukset, mutta ei täsmennä niiden jär-jestystä, kun taas US GAAP sallii suuremman joustavuuden. Lisäksi IFRS edellyttää, että vaih-tovelkakirjalainat jaetaan velka- ja omaisuuskomponentteihin, kun taas US GAAP luokittelee ne kokonaan veloiksi. Tutkimuksen tulokset vahvistavat teoriaa ja tarjoavat syvällisempää tie-toa erityisesti käytännön sovelluksista. IFRS-standardien ja US GAAP -standardien erot vaikut-tavat merkittävästi kansainvälisten markkinoiden taloudelliseen raportointiin, sijoittajien pää-töksiin ja yritysten strategioihin. Hycamiten on arvioitava huolellisesti IFRS-standardiin siirty-misen vaikutukset ja varmistettava yhteensopivuus US GAAP -standardin kanssa, jos sen yh-dysvaltalaiset yksiköt raportoivat tämän standardin mukaisesti. Tutkimus korostaa, miten IFRS- ja US GAAP -standardien erot vaikuttavat yrityksiin, sijoittajiin ja sääntelyviranomaisiin. Nämä erot vaikuttavat kansainvälisillä markkinoilla toimivien yritysten tilinpäätösten lä-pinäkyvyyteen, vertailukelpoisuuteen ja strategiseen päätöksentekoon.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business